LEGAL PROTECTION FOR OUTSOURCED WORKERS IN WAGES IN COMPANIES IN INDONESIA - Kadek Apriliani; I Nyoman Putu Budiartha; Johannes Ibrahim Kosasih; I Wayan Gde Wiryawan (Warmadewa Press, 2024)
Regarding the wage system for outsourced workers in companies in Indonesia, it has not been clearly regulated in Indonesian laws and regulations (Empty Norms), meaning that there is no law that specifically regulates wages for outsourced workers, so there is a need for legal protection for wages of outsourced workers. Based on these problems, the legal issues raised in this research are to analyze (1) the philosophical basis for regulating wages for outsourced workers, (2) the form of legal protection for the wages of outsourced workers in companies in Indonesia, (3) the legal construction of the wage model for outsourced workers. power in companies in Indonesia. The research method used is the normative legal research method. The results of the research show that (1) the philosophical basis for regulating wages for outsourced workers is to show that the state must protect every citizen for the sake of realizing general welfare as stated in paragraph 4 of the preamble to the 1945 Constitution of the Republic of Indonesia. (2) the form of legal protection for the wages of outsourced workers Companies in Indonesia must comply with the rights and obligations of workers, where it is clear that the laws and regulations regulate workers' wages in accordance with the Provincial Minimum Wage (referred to as UMP) The form of protection that can be given to transferred workers if there is a dispute between the worker and the outsourcing company is preventive legal protection and representative legal protection, both non-litigation and litigation. (3) the legal construction of the wage model for outsourced workers in companies in Indonesia aims to provide legal protection for outsourced workers and to resolve empty norms in Law of the Republic of Indonesia Number 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 Concerning Job Creation Becoming Law. The empty norms occur because Article 88 which regulates wages does not clearly regulate the wages of outsourced workers.